Equestrian Portrait of Cornelis (16391680) and Michiel Pompe van... - Aelbert Cuyp (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Equestrian Portrait of Cornelis (16391680) and Michiel Pompe van Meerdervoort (16381653) with Their Tutor and Coachman ("Starting for the Hunt"). Equestrian Portrait of Cornelis and Michiel Pompe van Meerdervoort with Their Tutor and Coachman is an equestrian portrait by Aelbert Cuyp, now held by the Metropolitan Museum of Art. This portrait is an early example of an equestrian portrait of someone who was not a member of court.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures